CRISPR-enabled investigation of fitness costs associated with the E198A mutation in β-tubulin of Colletotrichum siamense - Cosseboom, Scott D.; Agarwal, Chiti; Hu, Mengjun (Frontiers in Plant Science, 2023)
Understanding fitness costs associated with fungicide resistance is critical to improve resistance management strategies. E198A in β-tubulin confers resistance to the fungicide thiophanate-methyl and has been widely reported in several plant pathogens including Colletotrichum siamense. To better understand potential fitness costs associated with the resistance, a ribonucleoprotein (RNP) complex-mediated CRISPR/Cas9 system was used to create a point mutation (E198A) through homology directed repair (HDR) in each of the sensitive (E198) C. siamense isolates collected from strawberries, raspberries, and peaches. The RNP complex was delivered into fungal protoplasts using polyethylene glycol-mediated (PEG) transfection. The transformation efficiency, the proportion of transformants of sensitive parental isolates containing the E198A mutation, averaged 72%. No off-target mutations were observed when sequences similar to the β-tubulin target region with a maximum of four mismatch sites were analyzed, suggesting that the CRISPR/Cas9 system used in this study was highly specific for genome editing in C. siamense. Of the 41 comparisons of fitness between mutant and wild-type isolates through in vitro and detached fruit assays, mutant isolates appeared to be as fit (24 of 41 comparisons), if not more fit than wild-type isolates (10 of 41 comparisons). The use of CRISPR/Cas9 to evaluate fitness costs associated with point mutations in this study represents a novel and useful method, since wild-type and mutant isolates were genetically identical except for the target mutation.